Acoustic logic gates by a curved waveguide with ultrathin metasurfaces. (14th October 2019) - Lu, Yu-Jing; Ge, Yong; Yuan, Shou-Qi; Sun, Hong-Xiang; Liu, Xiao-Jun
Abstract: We report that an acoustic logic gate is realized by a three-port curved waveguide with four ultrathin curved metasurfaces immersed in air. By mechanically adjusting the angle positions of the curved metasurfaces, the transmission and phase of sound signals can be manipulated, and thus three basic logic functions OR, AND and NOT are realized in the same curved waveguide structure based on a linear interference mechanism. Moreover, the designed logic gate is also effective for two input signals with a certain phase difference, showing a high robustness in practical applications. Our designed logic gates have the advantages of constant structure configuration, passive phase modulation and high robustness, which have great potential applications in computing, information processing and integrated acoustics.